Education Management of Ulama Kader to Prepare Mubalig Competencies - Kusoy Anwarudin; Yosal Iriantara; Wiwik Dyah Aryani (UIN Sunan Gunung Djati Bandung, 2021)
The success of the Wasathiyah Islamic Clerical Cadre Education is inseparable from the extent to which MUI conducts an analysis of educational needs in the implementation of planning, organizing, implementing, monitoring and evaluating functions, methods, and learning processes as well as any obstacles faced by the West Java MUI during PKU. Based on the results of the research findings, it was revealed that the data on MUI Ulama Cadre Education (PKU) in West Java province contained the mission of